2005
DOI: 10.1021/jf050082g
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indicators of Cultured Newfoundland Blue Mussels (Mytilus edulis) during Storage on Ice:  Microbial Growth, pH, Lipid Oxidation, Chemical Composition Characteristics, and Microbial Fatty Acid Contents

Abstract: To devise proper strategies to evaluate and maintain the quality of cultured blue mussels (Mytilus edulis) during storage on ice, this study examined the potential use of microbial growth, pH, lipid oxidation, and composition characteristics as quality indicators. It also evaluated the use of individual (i15:0, ai15:0, i16:0, ai16:0, i17:0, ai17:0, 17:0) and total bacterial fatty acid contents as a rapid method to examine the microbial quality of stored mussels. Linear regression analyses of the storage period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…Additional fatty acid moieties detected were 14:0, 15:0, 17:0, 17:1, 18:0, 18:1, 18:2, 18:3, 18:4, 20:1, 20:2, 20:5 and 22:6, similar to those reported previously for OA/DTX1/DTX2,18, 23, 26, 36 for spirolides,41 and for PTX2 SA 42. Studies performed on the free fatty acid composition of blue mussels show that these are rich in palmitic acid (16:0), eicosapentaenoic acid (20:5) and docosahexaenoic acid (22:6), and fatty acids such as 14:0, 16:1 18:0, 18:1, 18:2, 18:3, 18:4, 20:1 and 20:2 are commonly present at substantial levels 40, 43–47. This corresponds well with the composition of fatty acid esters in the present study, as well as in previous studies 18, 23, 26, 37, 41, 42.…”
Section: Resultssupporting
confidence: 87%
“…Additional fatty acid moieties detected were 14:0, 15:0, 17:0, 17:1, 18:0, 18:1, 18:2, 18:3, 18:4, 20:1, 20:2, 20:5 and 22:6, similar to those reported previously for OA/DTX1/DTX2,18, 23, 26, 36 for spirolides,41 and for PTX2 SA 42. Studies performed on the free fatty acid composition of blue mussels show that these are rich in palmitic acid (16:0), eicosapentaenoic acid (20:5) and docosahexaenoic acid (22:6), and fatty acids such as 14:0, 16:1 18:0, 18:1, 18:2, 18:3, 18:4, 20:1 and 20:2 are commonly present at substantial levels 40, 43–47. This corresponds well with the composition of fatty acid esters in the present study, as well as in previous studies 18, 23, 26, 37, 41, 42.…”
Section: Resultssupporting
confidence: 87%
“…, 2004) even if some authors have suggested that bacterial analysis should be carried out in conjunction with sensory assessment (Boyd et al. , 1980; Khan et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of parameters has been used in the literature to assess bivalve quality (Khan et al. , 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, given this limited shelf life of fresh bivalves, it is unlikely to find significant differences in the FA profiles of the AM of control samples and the batch of bivalves being traded caused by the time frame between the collection of both (always ≤5 days). Although the dynamics of the FA profile of cockles during ice storage has never been assessed, a study performed on the whole body of blue mussels M. edulis revealed no major shifts on the FA profile during a 14-day storage period in ice37. Therefore, while it is likely that the FA profile of C. edule may remain stable during a 5-day storage period in ice, this assumption should be tested in the future, specifically for the adductor muscle of C. edule .…”
Section: Discussionmentioning
confidence: 99%